Experiences of Father Participattion in Caring for their Preterm Infants in a Sick Newborn Unit - Sarapat, Photjanart; Pongjaturawit, Yunee (Nursing Journal of The Ministry of Public Health, 2023)
The purpose of this descriptive qualitative study was to describe fathers’ experiences of participating in the care of their preterm infants in a sick newborn unit. Participants were purposive selected, including 13 fathers of preterm infants in a sick newborn unit of a government hospital in the Eastern Region. Data were collected using in-depth interviews and observations. Thematic analysis method was used to analyze the data. The results revealed that the experiences of father participation in caring for their preterm infants in a sick newborn unit can be divided into three themes. First, the feelings about preterm infant included anxiety and fear, pity and concern, unexpectedness, and happy with the birth of their infant. Second, the activities involved in caring for their infants, including physical care, psychological care, sharing information with doctors and nurses, supporting and encouraging mothers in caring for their infants, and providing utensils. Finally, the feelings about being involved in the care of their infants included being happy, loving and preferring to do something for their infants, having learned to care for their infants, reducing the burden of mothers’ tasks, and being unconfident in the care of their infants. These findings contribute to a better understanding of fathers’ experiences in caring for their preterm infants in a sick neonatal unit. Therefore, nurses and health care providers could use the data as a basis to encourage and support fathers to participate effectively in caring for their preterm infants in a sick neonatal unit.